NEW EARLY CRETACEOUS TRIGONIIDS (BIVALVIA) FROM THE CRIMEA AND NORTHERN CAUCASUS - Yanin B.T. (My University, 2004)
Six new species and one subspecies of the family Trigoniidae (Bivalvia) are described: Trigonia carinata crimica and Myophorella tonasensis from the Berriasian of the Crimea, Rutitrigonia balaklavensis and Pterotrigonia taurica from the Albian of the Crimea, Pterotrigonia druzczici from the Aptian of the northern Caucasus, and Linotrigonia kudryavzevi and L. plana from the Barremian of the northern Caucasus.
Keywords: Trigoniidae; Mesozoic::Cretaceous; Мезозой::Меловая